The influence of spatial resolution on macroecological patterns of range size variation: a case study using parrots (Aves: Psittaciformes) of the world - Tim M. Blackburn; Kate E. Jones; Phillip Cassey; Neil Losin (Journal of Biogeography, 2004)
Aim To assess the extent to which the resolution at which geographical range sizes are measured influences macroecological patterns in this variable. Location Global. Methods Data on the geographical ranges of parrot species were digitized, and a Geographic Information System used to produce nine range size estimates for each species using different degrees of spatial resolution. The inter‐correlation of these estimates was then compared, together with their patterns of covariation with population size, body mass and migratory behaviour (across species and controlling for phylogeny), their pattern of phylogenetic correlation, and the frequency distributions of the different measures. Results Strong correlations exist among all nine range size measures across species, albeit that measures of similar spatial resolution are more strongly correlated. All measures show similar patterns of covariation with population size, body mass and migratory behaviour, and similar patterns of phylogenetic correlation. The skewness of frequency distributions increases towards zero as the resolution of the range size measure declines. Main conclusions The results of macroecological analyses are little affected by the resolution with which geographical range sizes are calculated, at least for the parrots of the world. Previously published studies based on crude measures of range size would be unlikely to have produced markedly different conclusions had they used more refined range size metrics.